(untitled) (Annals of Medical Research, 2024)
Aim: Pyogenic granuloma (PG), also known as lobular capillary hemangioma, is a benign, reactive vascular tumor. We aimed to evaluate the demographic and clinical characteristics, treatments received, and outcomes of patients followed up at our clinic with PG. Materials and Methods: We retrospectively evaluated all patients followed up at our clinic with PG in the last 4 years. Results: A total of 144 patients were included in our study. 73 (51%) of the patients were female and 71 (49%) were male. The mean age of the patients was 31.3±8.3 years. When we examined the PG locations in our patients, we observed that it was most commonly found in the arm/hand area (40%), on the face (29%), foot/leg area (19%), and on the trunk (8.3%). The highest numbers of lesions were respectively in the hand, foot nail edge, and lip locations. Out of the patients where the lesion side was specified, 63 had the lesion on the left while 20 had it on the right (p=0.001). 51% of our patients underwent excisional surgery. Other treatments applied to our patients, in order, were cryotherapy (15.3%), electrocauterization (8.3%), and cauterization with silver nitrate, cryotherapy + electrocauterization, topical antibiotic and cryotherapy + timolol drop. When evaluating the outcomes of the patients, we learned from the notes dropped into the system at later controls that 73% had recovered. The remaining patients were lost to follow-up. When comparing the features of patients who were treated with non-excisional methods to those who underwent excision, we observed that there was a higher rate of patients younger than 12 years (p=0.023), a higher incidence of foot nail edge (p=0.016) and lip location (p=0.048), and a higher frequency of pregnancy in this group. Conclusion: PG is a vascular tumor of importance due to its potential for bleeding and ulceration and its chronic course if left untreated. Since there are malignant lesions in its differential diagnosis, we believe that surgical excision is a more appropriate treatment option in our clinical practice when feasible. We think that the data we have obtained needs to be supported by more comprehensive, broader, and prospective studies.